Quantum-Resistant Security for IoT Systems: Challenges and Implementation Strategies - Amit Awasthi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The imminent arrival of quantum computing presents unprecedented challenges to Internet of Things (IoT) security, threatening to compromise the cryptographic protocols that safeguard billions of connected devices worldwide. This article examines the critical intersection of quantum computing capabilities and IoT vulnerabilities, with particular emphasis on resource-constrained devices, heterogeneous networks, and legacy system integration. This article presents a comprehensive framework for implementing quantum-resistant security measures in IoT environments, introducing a hybrid approach that combines lightweight quantum-resistant algorithms with modular architecture design. This article demonstrates traditional encryption methods like RSA and ECC remain vulnerable to quantum attacks; strategic implementation of lattice-based and hash-based cryptography can provide robust protection without overwhelming device resources. This article also addresses practical considerations for industry adoption, including development lifecycle integration, governance frameworks, and compliance requirements. Through examination of real-world implementation scenarios, this article establishes a successful quantum-resistant IoT security required for a balanced approach between immediate protective measures and long-term strategic planning, providing organizations with actionable guidelines for securing their IoT infrastructure against quantum threats.